Selective Degradation of MLK3 by a Novel CEP1347-VHL-02 PROTAC Compound Limits the Oncogenic Potential of TNBC - Karpińska, Kamila; Mehlich, Dawid; Sabbasani, Venkata R.; Łomiak, Michał; Torres-Ayuso, Pedro; Wróbel, Katarzyna; Truong, Vi Nguyen-Phuong; Serwa, Remigiusz; Swenson, Rolf E.; Brognard, John; Marusiak, Anna A. (Journal of medicinal chemistry, 2024)
Triple-negative breast cancer (TNBC) is associated with poor prognosis because of the lack of effective therapies. Mixed-lineage protein kinase 3 (MLK3) is a protein that is often upregulated in TNBC and involved in driving the tumorigenic potential of cancer cells. Here, we present a selective MLK3 degrader, CEP1347-VHL-02, based on the pan-MLK inhibitor CEP1347 and a ligand for E3 ligase von Hippel-Lindau (VHL) by employing proteolysis-targeting chimera (PROTAC) technology. Our compound effectively targeted MLK3 for degradation via the ubiquitin-proteasome system in several cell line models but did not degrade other MLK family members. Furthermore, we showed that CEP1347-VHL-02 robustly degraded MLK3 and inhibited its oncogenic activity in TNBC, measured as a reduction of clonogenic and migratory potential, cell cycle arrest, and the induction of apoptosis in MDA-MB-468 cells. In conclusion, we present CEP1347-VHL-02 as a novel MLK3 degrader that may be a promising new strategy to target MLK3 in TNBC.